Analysis of performances at the `Ironman Hawaii triathlon` and its qualifier events with respect to nationality - Stiefel, M.; Knechtle, B.; Rüst, C. A.; Rosemann, T. (Journal of Science and Cycling, 2013)
The Ironman World Championship in Hawaii is assumed to be the most challenging Ironman triathlon in the world. Athletes intending to compete in `Ironman Hawaii` need to qualify. The aims of this study were (i) to compare the participation of athletes between `Ironman Hawaii` and its qualifier races regarding their origin, and (ii) to compare the top ten performances of selected nations in `Ironman Hawaii` with the top ten performances of the same nations in qualifier races within one year. All finishers in 2010 in both `Ironman Hawaii` and in the qualifier races were analyzed regarding nationality, sex and performance of finishers. For women, a higher percentage (27.2%) finished in `Ironman Hawaii` compared to the qualifiers (18.9%). For men, a higher percentage (81.1%) finished in the qualifiers compared to `Ironman Hawaii` (72.8%). In both `Ironman Hawaii` and in the qualifiers, most finishers originated from the USA, followed by athletes from Germany and Canada. When the split and overall race times of the top ten finishers of the fastest nations were compared between the qualifiers and `Ironman Hawaii`, split and overall races times were faster in both women and men in the qualifiers compared to `Ironman Hawaii`. In the qualifiers, the fastest women originated from the USA (551±14 min), followed by athletes from Germany (563±12 min) and Switzerland (574±22 min). In `Ironman Hawaii` the fastest race times were achieved by American women (571±10 min), followed by women originating from Australia (600±32 min) and Germany (623±25 min). For men, the fastest race times in the qualifiers were reached by athletes originating from Germany (496±7 min), followed by athletes from Australia (503±10 min) and Great Britain (512±9 min). In `Ironman Hawaii`, American triathletes (522±11 min) were the fastest followed by German (526±19 min) and Australian (532±26 min) finishers. These findings showed that (i) split and overall race times were slower in `Ironman Hawaii` compared to its qualifiers and (ii) American triathletes dominated both participation and performance in both `Ironman Hawaii` and its qualifiers.